Phytochemical Profiling and In Silico Screening of Bioactive Compound From Persea americana Mill. as Cyclooxygenase-2 Inhibitors - Aisyah, Aisyah; Utami, Wiji; Fitria, Dori; Faadila, Ayu; Juliyanti, Juliyanti (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Pharmacological information on avocado leaves has been studied through phytochemistry, Lipinski, ADMET, protein ligand interactions, molecular docking, density functional theory (DFT), and molecular dynamics. This study aims to determine the secondary metabolite content of avocado leaf extracts using phytochemical screening methods and to assess the ability of bioactive compounds to inhibit cyclooxygenase-2 through molecular docking calculations using the PDB ID 5IKR. Phytochemical screening showed that the ethanol extract contained alkaloids, saponins, tannins, steroids, and flavonoids, while the ethyl acetate fraction lacked saponins. In addition, most of the compounds met the Lipinski and ADMET rules. Avocadene and hippuric acid are potential candidate agents with binding energies of -5.73 kcal/mol and -5.41 kcal/mol, respectively. The binding interaction of avocadene and hippuric acid with the COX-2 receptor is reinforced by hydrogen bonds with MET490 and TYR353. Avocadene exhibits a higher HOMO-LUMO energy gap (7.146 eV) than hippuric acid (5.176 eV). Molecular dynamics simulations confirmed the stability of both complexes, with RMSD values of 1.769 and 1.791 Å, respectively, and showed no significant fluctuations throughout the 100 ns simulation. This study provides a foundation for the development of natural-product-based drugs for inflammatory diseases and requires future in vitro and in vivo validation. Abstrak: Informasi farmakologi pada daun alpukat telah diteliti melalui fitokimia, Lipinski, ADMET, interaksi protein ligand, molekuler docking, density functional theory (DFT) dan dinamika molekuler. Penelitian ini bertujuan untuk menentukan kandungan metabolit sekunder pada ekstrak daun alpukat menggunakan metode skrining fitokimia serta mengevaluasi kemampuan senyawa bioaktif dalam menghambat siklooksigenase-2 melalui perhitungan docking molekuler menggunakan PDB ID 5IKR. Penyaringan fitokimia menunjukkan bahwa ekstrak etanol mengandung alkaloid, saponin, tanin, steroid, dan flavonoid, sedangkan fraksi etil asetat tidak mengandung saponin. Selain itu, sebagian besar senyawa memenuhi aturan Lipinski dan ADMET. Avocadene dan hippuric acid sebagai kandidat agen potensial dengan energi ikatan masing-masing sebesar -5,73 kcal/mol dan -5,41 kcal/mol. Interaksi ikatan avocadene dan asam hippurat dengan reseptor COX-2 diperkuat oleh ikatan hidrogen dengan MET490 dan TYR353. Avocadene menunjukkan celah energi HOMO-LUMO yang lebih tinggi (7,146 eV) dibandingkan hippuric acid (5,176 eV). Simulasi dinamika molekuler mengonfirmasi stabilitas kedua kompleks tersebut, dengan nilai RMSD masing-masing sebesar 1,769 dan 1,791 Å, serta tidak menunjukkan fluktuasi yang signifikan selama simulasi 100 ns. Penelitian ini memberikan landasan untuk pengembangan obat berbasis produk alami untuk penyakit inflamasi dan membutuhkan validasi in vitro dan in vivo di masa mendatang.